The contribution of Acad. N.A. Puchkovskaia to advances in ocular trauma management (Ukrainian Journal of Ophthalmology, 2026)
The paper has sought to summarize the contribution of Acad. N.A. Puchkovskaia to advances in the understanding, treatment and care of people with eye trauma. The unified emergency eye trauma care system was established in Ukraine through her initiative to provide high-quality emergency care in severe ocular trauma not at the injured person’s place of residence but at a specialized care center to which s/he is transported in emergency. The techniques that N.A. Puchkovskaia developed to manage traumatic eye injuries (like superficial therapeutic lamellar keratoplasty technique for surgical processing of corneal lacerations, “keratoplasty with two grafts” for the treatment of traumatic corneal defects, advanced techniques for IOFB removal from hard-to-access eye areas, and tissue homografts for extensive traumatic corneal and scleral injuries) are still successfully used today. The ultrasonic and laser technologies that she proposed to use in ocular trauma management were further developed. The Ocular Trauma Department that was established at the Filatov Institute through the initiative of N.A. Puchkovskaia 55 years ago, maintains the basic principles of management for eye injuries, and is a Ukrainian leader in providing specific medical care to the critically injured eye trauma patient.